High performance bio-supercapacitor electrodes composed of graphitized hemicellulose porous carbon spheres - Zhang, Zhili; Li, Fengfeng; Chen, Jiachuan; Yang, Guihua; Ji, Xingxiang; Tian, Zhongjian; Wang, Baobin; Zhang, Lei; Lucia, Lucian (Frontiers in Bioengineering and Biotechnology, 2022)
A template-free and one-step carbonization process was developed for fabricating graphitic porous carbon spheres (GPCSs) on hemicelluloses as the electrode material for supercapacitors. This method is green, low-energy, and less time consuming compared to the conventional two-step process (pore-forming & graphitizing). It uses K2FeO4, a mild activating agent that fulfills synchronous activation and graphitization. The GPCSs is regular spherical shape, have high nanoporosity, a large specific surface area (1250 m2 g-1), and have a high graphitization degree. A unique structural advantage includes a rich interconnected conductive network for electron transfer that shortens the ion transport distance of the electrolyte. Remarkably, the GPCSs electrode displays outstanding electrochemical performance including high specific capacitance (262 F g-1 at 1.0 A g-1), rate capability energy (80%, 20 A g-1), and excellent cycling stability (95%, 10,000 cycles). This work represents a powerful methodology to develop sustainable and low-cost energy storage devices from hemicellulose.